2018
DOI: 10.1128/iai.00526-18
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Enterotoxigenic Escherichia coli Heat-Stable Toxin Secretion and Delivery

Abstract: Enterotoxigenic (ETEC), a heterogeneous diarrheal pathovar defined by production of heat-labile (LT) and/or heat-stable (ST) toxins, causes substantial morbidity among young children in the developing world. Studies demonstrating a major burden of ST-producing ETEC have focused interest on ST toxoids for ETEC vaccines. We examined fundamental aspects of ST biology using ETEC strain H10407, which carries and genes encoding STh and STp, respectively, in addition to genes responsible for LT. Here, we found that d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 62 publications
(59 reference statements)
0
23
0
Order By: Relevance
“…Both ST subtypes contribute to disease symptoms, 25 although the relative amounts produced by a particular ETEC strain may vary. 26 In the next assessment of the infection model, we evaluated total ST secretion (ST h and ST p ) and subsequent induction of cGMP production in HEMs following exposure to WT H10407 or mutant strains deficient in ST h , ST p , LT, EatA, EtpA, or CfaE expression ( Figure 2a ). Each of the mutants (other than ST-targeted mutations) secreted approximately equivalent amounts of ST compared to WT, suggesting no impairment in ST synthesis or release mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ST subtypes contribute to disease symptoms, 25 although the relative amounts produced by a particular ETEC strain may vary. 26 In the next assessment of the infection model, we evaluated total ST secretion (ST h and ST p ) and subsequent induction of cGMP production in HEMs following exposure to WT H10407 or mutant strains deficient in ST h , ST p , LT, EatA, EtpA, or CfaE expression ( Figure 2a ). Each of the mutants (other than ST-targeted mutations) secreted approximately equivalent amounts of ST compared to WT, suggesting no impairment in ST synthesis or release mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of intracellular cAMP and cGMP in HEMs colonized by H10407 was recently reported. 24,26 However, the characterization of infection-associated cyclic nucleotide efflux has not been explored in the HEM model. Additionally, evaluation of an approximate pathophysiological ST concentration for experimental reference has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, intracellular cGMP accumulation was markedly restricted by phosphodiesterase PDE5-mediated degradation in enteroids and colonoids, whereas Caco-2 and T84 polarized monolayers incubated with ST yielded high amounts of both intracellular and extracellular cGMP. Toxin delivery by ETEC is known to be enhanced by several virulence factors, 96 and this was reinforced in the observed dependence on expression of adhesins CFA/I and EtpA and the mucinase EatA by ETEC H10407 to elicit ST-induced cGMP production in enteroids.…”
Section: Enterotoxigenic E Coli (Etec)mentioning
confidence: 97%
“…These intramolecular disulfide bridges ensure correct folding of the mature STa peptide, which closely resembles that of two mammalian peptides, guanylin and uroguanylin, and are important for its function [41]. Secretion of mature STh and STp into the extracellular environment requires the efflux protein TolC (Figure 1) [42]. Interestingly, these authors also showed that the propeptide (pro-STh) is secreted, reaffirming earlier reports on propeptide secretion by human ETEC strains [43].…”
Section: Heat-stable Enterotoxins Of Etec From Human and Animal Ormentioning
confidence: 99%